Greek Χαριτες – Armenian Ձիրք - HARUTYUNYAN, TSOVINAR (Bulletin of Yerevan University B: Philology, 2021)
The name of three Graces Χαριτες pl. t. (the plural form of xαρις “beauty, delight, blossom”) by now has been translated into Latin as Gratiae pl.t. (the plural form of gratia “attractiveness, gratefulness, grace”) and refers to the names of goddesses inGreek and Latin. Other languages also use these names. This article presents a study based on several etymological analyses of the nouns xαρις and gratia, and particularly, the adverbial use of their ablative cases. In this regard, drawing etymological parallels with their Armenian equivalents ձիր (noun) “donation, gift, favour, bliss” and ձրի (adverb) “donate, for free, gratis”, we assume that the word Ձիրք pl.t. “talent, gift”, which is the plural form of the Armenian word ձիր, is the Armenian equivalent of the names of the goddesses mentioned above.